Accessing local markets: Marketsheds - Guo, Zhe; Cox, Cindy M. (International Food Policy Research Institute, 2014)
Across Africa buying and selling connects people. For a small-scale farmer, this trade takes place primarily within a limited geographic area based on access to market centers of a given size. The maps illustrate these areas using different colors to represent marketsheds—geographical areas and associated populations that are part of real or potential trade networks with a given market. From any location within a marketshed, it takes less time to travel to the corresponding market compared to any neighboring markets. In theory, farmers within a marketshed prefer to trade their commodities at the corresponding market, which minimizes travel cost (p. 66).